Comparative Whole-Genome Phylogeny of Animal, Environmental, and Human Strains Confirms the Genogroup Organization and Diversity of the Stenotrophomonas maltophilia Complex - Mercier-Darty, Mélanie (Appl Environ Microbiol, 2020)
The Stenotrophomonas maltophilia complex (Smc) comprises opportunistic environmental Gram-negative bacilli responsible for a variety of infections in both humans and animals. Beyond its large genetic diversity, its genetic organization in genogroups was recently confirmed through the whole-genome sequencing of human and environmental strains. As they are poorly represented in these analyses, we sequenced the whole genomes of 93 animal strains to determine their genetic background and characteristics. Combining these data with 81 newly sequenced human strains and the genomes available from RefSeq, we performed a genomic analysis that included 375 nonduplicated genomes with various origins (animal, 104; human, 226; environment, 30; unknown, 15). Phylogenetic analysis and clustering based on genome-wide average nucleotide identity confirmed and specified the genetic organization of Smc in at least 20 genogroups. Two new genogroups were identified, and two previously described groups were further divided into two subgroups each. Comparing the strains isolated from different host types and their genogroup affiliation, we observed a clear disequilibrium in certain groups. Surprisingly, some antimicrobial resistance genes, integrons, and/or clusters of attC sites lacking integron-integrase (CALIN) sequences targeting antimicrobial compounds extensively used in animals were mainly identified in animal strains. We also identified genes commonly found in animal strains coding for efflux systems. The result of a large whole-genome analysis performed by us supports the hypothesis of the putative contribution of animals as a reservoir of Stenotrophomonas maltophilia complex strains and/or resistance genes for strains in humans. IMPORTANCE Given its naturally large antimicrobial resistance profile, the Stenotrophomonas maltophilia complex (Smc) is a set of emerging pathogens of immunosuppressed and cystic fibrosis patients. As it is group of environmental microorganisms, this adaptation to humans is an opportunity to understand the genetic and metabolic selective mechanisms involved in this process. The previously reported genomic organization was incomplete, as data from animal strains were underrepresented. We added the missing piece of the puzzle with whole-genome sequencing of 93 strains of animal origin. Beyond describing the phylogenetic organization, we confirmed the genetic diversity of the Smc, which could not be estimated through routine phenotype- or matrix-assisted laser desorption ionization–time of flight mass spectrometry (MALDI-TOF)-based laboratory tests. Animals strains seem to play a key role in the diversity of Smc and could act as a reservoir for mobile resistance genes. Some genogroups seem to be associated with particular hosts; the genetic support of this association and the role of the determinants/corresponding genes need to be explored.